Margaiostus sundukovi sp. nov., the first record of the genus in the Palaearctic region (Coleoptera: Elateridae) - Prosvirov, Alexander S. (Zootaxa, 2015)
The genus Margaiostus Stibick, 1978, previously known from North and South America, is recorded for the first time in the fauna of the Palaearctic region. M. sundukovi sp. nov. is described from the Far East of Russia. The position of this species within the genus and the distribution of Margaiostus are discussed.